Zardozi Artifacts and Their History in the Bukhara Museum - Sultonova Nigina (Scientific Trends, 2025)
This article explores the rich artistic and historical heritage of Bukhara’s gold embroidery art - zarduzi, one of the most exquisite and ancient forms of applied decorative art in Central Asia. It examines the evolution of gold embroidery techniques such as zarduzi-zaminduzi and zarduzi-gulduzi, highlighting their aesthetic sophistication and social significance within the Emirate of Bukhara. The study traces the craft’s development from the medieval period through its flourishing during the reigns of Emirs Muzaffar Khan and Abdulahad Khan, to its decline and revival in later centuries. Special attention is given to the organization of palace and private workshops, the socio-economic status of artisans, and the luxurious garments produced for the Emir’s court. The article also discusses unique surviving examples of zarduzi masterpieces preserved in the Sitorai Mokhi-Khosa Museum and the Bukhara State Museum-Reserve, emphasizing their exceptional craftsmanship, historical authenticity, and cultural symbolism. Through this analysis, the paper demonstrates how Bukhara’s zarduzi tradition continues to serve as a vital expression of Uzbekistan’s national identity and intangible cultural heritage.
Keywords: Bukhara Emirate, zarduzi, gold embroidery, decorative art, cultural heritage, applied arts, Sitorai Mokhi-Khosa, Emir Abdulahad Khan, Muzaffar Khan, traditional crafts, Uzbekistan.